Valorization of fish processing waste: a microbial perspective - Embrandiri, Asha; Rupani, Parveen Fatemeh; Mohamad, Mohd Azrul Naim; Jamaludin, Mohd Hafiz (Springer International Publishing AG, 2018)
In recent years, there has been a steady increase in the exploitation of fish resources and the estimated quantity used for human consumption globally is about 75% of the worldwide fish production (105.6 million tons).